RETRACTED: The Effect of Work Environment, Workload and Financial Incentives on Employee Performance at PT. Indofood CBP Sukses Makmur Tbk - Muhammad Nuryadin; Ahmad Cik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The purpose of this study is to determine whether there is an influence of the Work Environment, Workload and Financial Incentives on Employee Performance at PT. Indofood CBP Sukses Makmur Tbk. By paying attention to the level of HR in the company, it is expected to make a real contribution to improving employee performance results. This research method uses a quantitative approach with correlational or causal studies. The research site is located on Jalan Raya Cikopo, Cikopo, Kec. Bungursari, Kab. Purwakarta, West Java 41181. The subjects of this research are individual employees who work at PT. Indofood CBP Sukses Makmur Tbk. This study uses primary data with data techniques using a questionnaire via google form to 72 employees. The instrument test uses validity and reliability tests. The data analysis technique used is multiple regression analysis which is operated through the SPSS 23 program. The results showed that there was a relationship between the variables of Work Environment, Workload and Financial Incentives on Employee Performance at PT. Indofood CBP Success Makmur. Partially significant effect on the relationship between the dependent variable (Y) and the independent variable (X). Suggestions that need to be considered for the company’s internal parties to continue to maintain the quality of employee performance by paying attention to all supporting aspects, namely variable X.